Effects of accounting disclosure regulation on the Singapore securities market - Williams, John Joseph (2008)
This paper critically reviews the issues, conflicts, and implications associated with the mandated disclosure requirement by the Stock Exchange of Singapore for firms with bond-cum-warrant financial instruments.